Mid-arm muscle area and anthropometry predict low birth weight and poor pregnancy outcomes in Tanzanian women with HIV - Paul Petraro; Isabel Madzorera; Christopher P. Duggan; Donna Spiegelman; Karim Manji; Rodrick Kisenge; Roland Kupka; Wafaie W. Fawzi (BMC, 2018)
Abstract Background An observational study was conducted to examine the role of maternal anthropometry, including mid-arm muscle area (MAMA) and others, as risk factors for low birth weight (LBW), small for gestational age (SGA) and preterm births in human immunodeficiency virus (HIV) infected pregnant women. HIV-positive women (N = 2369), between 12 and 32 weeks gestation were followed through delivery in Tanzania, from 2003 to 2008. Participants were women enrolled in a randomized, double-blind, placebo-controlled, clinical trial who delivered live births. Methods Binomial regression analysis was used to evaluate the association of maternal nutritional indicators of MAMA, mid-upper arm circumference (MUAC), body mass index (BMI) and maternal weight with LBW, SGA and preterm in multivariate analysis. Results Higher MAMA was associated with a 32% lower risk of LBW compared to lower measurements (RR = 0.68, 95% CI = 0.50-0.94). Similar protective associations were noted for higher BMI (RR = 0.58, 95% CI = 0.42-0.79); maternal weight (RR = 0.50, 95% CI = 0.36-0.69) and MUAC (RR = 0.62, 95% CI = 0.45-0.86). Higher MAMA was also associated with lower risk of SGA (RR = 0.78, 95% CI = 0.68-0.90) and marginally associated with preterm (RR = 0.85, 95% CI = 0.69-1.04). Beneficial associations of MUAC, BMI and maternal weight with SGA and preterm were also observed. Conclusion MAMA performs comparably to MUAC, maternal weight and BMI, as a predictor of LBW and SGA in HIV-infected women. The possible role of MAMA and other indicators in screening HIV positive women at risk of adverse pregnancy outcomes should be investigated.